Healthy lifestyle and the risk of pancreatic cancer in the EPIC study - Naudin, Sabine (Eur J Epidemiol, 2020)
BACKGROUND: Pancreatic cancer (PC) is a highly fatal cancer with currently limited opportunities for early detection and effective treatment. Modifiable factors may offer pathways for primary prevention. In this study, the association between the healthy lifestyle index (HLI) and PC risk was examined. METHODS: Within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort, 1,113 incident PC (57% women) were diagnosed from 400,577 cancer-free participants followed-up for 15 years (median). HLI scores combined smoking, alcohol intake, dietary exposure, physical activity and, in turn, overall and central adiposity using BMI (HLI(BMI)) and waist-to-hip ratio (WHR, HLI(WHR)), respectively. High values of HLI indicate adherence to healthy behaviors. Cox proportional hazard models with age as primary time variable were used to estimate PC hazard ratios (HR) and 95% confidence intervals (CI). Sensitivity analyses were performed by excluding, in turn, each factor from the HLI score. Population attributable fractions (PAF) were estimated assuming participants’ shift to healthier lifestyles. RESULTS: The HRs for a one-standard deviation increment of HLI(BMI) and HLI(WHR) were 0.84 (95% CI: 0.79, 0.89; p(trend)=4.3e-09) and 0.77 (0.72, 0.82; p(trend)=1.7e-15), respectively. Exclusions of smoking from HLI(WHR) resulted in HRs of 0.88 (0.82, 0.94; p(trend)=4.9e-04). The overall PAF estimate was 19% (95% CI: 11%, 26%), and 14% (6%, 21%) when smoking was removed from the score. CONCLUSION: Adherence to a healthy lifestyle was inversely associated with PC risk, beyond the beneficial role of smoking avoidance. Public health measures targeting compliance with healthy lifestyles may have an impact on PC incidence.